Sanz y Escartín and social thought of the Church - Campo Sánchez, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Sanz and Escartín is one of the first Spanish sociologists. Catholic thinker, and conservative politics, decisively influenced Spanish reformist thinking. Of the various sources from which emphasizes drank Christian social thought. Before the publication of Rerum Novarum had advocated in his writings positions and approaches that, following the publication of the Encyclical, became part of the social doctrine of the Church. Issues of ethical-religious social reform, the central role of the Church, the legitimacy of state intervention and the need for alternative association of workers and employers are some of the elements present in the work of Sanz and Escartín.